Direct selling as the first choice career / Nor Aina Kamilah Mohd Azam - Mohd Azam, Nor Aina Kamilah (2011)
This study was aim mainly to focus on the direct selling as the first choice career. The purpose of this study was to identify the reasons why people involve in direct selling, whether direct selling promise a better future and to identify whether direct selling can be a first choice career. 100 questionnaires were distributed to the respondents whether they were involved in direct selling or not. The frequency distribution, cross tabulation and chi-square were used in order to analyze the data and to find out the relationship between direct selling as the first choice career with freedom, social interaction, risk and recognition. Thus, the finding from this study showed that all the variables had the significant relationship with direct selling as the first choice career